Evaluation of Vaginal Cysts and Masses by 3‐Dimensional Endovaginal and Endoanal Sonography. (1st August 2013) - Shobeiri, S. Abbas; Rostaminia, Ghazaleh; White, Dena; Quiroz, Lieschen H.; Nihira, Mikio A.
Abstract : The purpose of this pictorial essay is to describe the utility of 3‐dimensional endovaginal and endoanal sonography in the assessment of vulvovaginal cysts and masses. It is accepted that compared with transabdominal pelvic sonography, transvaginal end‐fire sonography provides improved resolution for visualization of female reproductive organs with fewer artifacts. To visualize the structures that are located in or lateral to the vaginal canal, side‐fire 3‐dimensional endovaginal or endoanal sonography can be used. This special technique has the advantage of maintaining the spatial anatomic relationship of any abnormality in the vagina.